Educação financeira - Souza, Alisson Coutinho de (2021)
Financial education walks side by side along with mathematical education, and there are no doubts that more and more a necessity to offer a great amount of people, from all sorts of ages, solid education on finances is demanded. This can be accomplished through basic education of Math classes either in elementary school and in high school, so that we could develop in children, young adults and adults some skills and proficiency which will allow them to take financial decisions that are safer and more conscious. Any family’s financial health demands knowledge and discipline. That’s the reason of this Project, to propose that mathematical knowledge offered to students can be transmitted on the basis of the need to develop their skills needed to sort out any financial decision taking. However, Brazil’s basic education evaluation system (SAEBE), shows that our students’ learning level of Math is rather low and financial international exams as PISA, confirm this reality: The lack of a good mathematical education, contributes to a low level of a financial education in the whole population. Therefore, it is demanding the tools which gather these two knowledge fields. Our Project has its goal the elaboration of a book on financial education which could be used by students in the early grades of high school and could offer the complete theoretical foundation needed in order to students understand the basic concepts of financial education and to become adults totally capable of managing the best way possible the resources generated by their workforce, assuring a better future for themselves and their family members.